Developing an Evidence-Based Coexistence Strategy to Promote Human and Wildlife Health in a Biodiverse Agroforest Landscape - Bersacola, Elena; Parathian, Hannah; Frazão-Moreira, Amélia; Jaló, Maimuna; Sanhá, Américo; Regalla, Aissa; Saíd, Abílio Rachid; Quecuta, Queba; Camará, Samba Tenem; Quade, Sara Marunur Faria Fernandes; Jaquite, Sidi Mohamed; Lopes, Aristoteles Gomes; et al. (Frontiers in Conservation Science, 2021)
Agroforest mosaics represent one of the most extensive human-impacted terrestrial systems worldwide and play an increasingly critical role in wildlife conservation. In such dynamic shared landscapes, coexistence can be compromised if people view wildlife as a source of infectious disease. A cross-disciplinary One Health knowledge base can help to identify evolving proponents and threats to sustainable coexistence and establish long-term project goals. Building on an existing knowledge base of human-wildlife interactions at Cantanhez National Park (NP), Guinea-Bissau, we developed a causal pathway Theory-of-Change approach in response to a newly identified disease threat of leprosy in the Critically Endangered western chimpanzee (Pan troglodytes verus). The goals of our project are to improve knowledge and surveillance of leprosy in humans and wildlife and increase capacity to manage human-wildlife interactions. We describe the core project activities that aim to (1) quantify space use by chimpanzees across Cantanhez NP and determine the distribution of leprosy in chimpanzees; (2) understand the health system and local perceptions of disease; and (3) identify fine-scale risk sites through participatory mapping of resources shared by humans and chimpanzees across target villages. We discuss the development of a biodiversity and health monitoring programme, an evidence-based One Health campaign, and a One Health environmental management plan that incorporates the sharing of space and resources, and the disease implications of human-nonhuman great ape interactions. We demonstrate the importance of multi-stakeholder engagement, and the development of strategy that fully considers interactions between people, wildlife, and the environment.